PENGARUH KOMITE AUDIT DAN KUALITAS AUDIT TERHADAP PENGHINDARAN PAJAK (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2019) - Pingkan Meilintang; Lihan Rini Puspo Wijaya; Destia Pentiana (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2022)
Tax revenues are still the largest contributor with a contribution of 82% of the total state revenues that are useful in the implementation of national development. However, the purpose of the government to maximize revenue from the taxation sector is contrary to the objectives of the company as a taxpayer. In accordance with the assumption that taxes are considered a burden, there is a desire to reduce taxes through tax avoidance. Supervision and expediatory of audit planning conducted by the company to reduce the tax burden then the responsibility is given to the audit committee. An audit committee with the authority it has will be able to prevent deviant actions related to the company's financial statements. So that with the audit committee in the company can minimize the occurrence of tax avoidance practices.  In addition, the quality of audits is getting better, and it will be increasingly difficult to do tax avoidance. Based on the exposure, researchers want to know the influence of the audit committee and the quality of audits on tax avoidance. This research was conducted on 57 manufacturing companies registered with the IDX 2017-2019. Research uses secondary data and data sources from the res IDX website. The analysis conducted on this study is a test of classical assumptions and multiple regressions. The results of the study found that the audit committee partially affected tax avoidance and the quality of audits partially had no effect on the tax enforcement of manufacturing companies.